2008
DOI: 10.1371/journal.pone.0002836
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Human Gut Microbiota by Barcoded Pyrosequencing

Abstract: Humans host complex microbial communities believed to contribute to health maintenance and, when in imbalance, to the development of diseases. Determining the microbial composition in patients and healthy controls may thus provide novel therapeutic targets. For this purpose, high-throughput, cost-effective methods for microbiota characterization are needed. We have employed 454-pyrosequencing of a hyper-variable region of the 16S rRNA gene in combination with sample-specific barcode sequences which enables par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
770
8
9

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 924 publications
(834 citation statements)
references
References 36 publications
47
770
8
9
Order By: Relevance
“…The recently developed 454 pyrosequencing approach, using multiple sequence tags or barcodes, allows for relatively deep sequencing of multiple samples in parallel at fairly high taxonomic resolution, although not at a level equal to that of full-length 16S rRNA sequencing (Sogin et al, 2006;Andersson et al, 2008). The power of this method was recently demonstrated in a sequencing study of human fecal samples that resulted in 440,000 reads with an average read length of 59 bp (Dethlefsen et al, 2008).…”
Section: Methods To Analyze the Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…The recently developed 454 pyrosequencing approach, using multiple sequence tags or barcodes, allows for relatively deep sequencing of multiple samples in parallel at fairly high taxonomic resolution, although not at a level equal to that of full-length 16S rRNA sequencing (Sogin et al, 2006;Andersson et al, 2008). The power of this method was recently demonstrated in a sequencing study of human fecal samples that resulted in 440,000 reads with an average read length of 59 bp (Dethlefsen et al, 2008).…”
Section: Methods To Analyze the Microbiotamentioning
confidence: 99%
“…Approximately 800 to 1,000 different bacterial species and more than 7,000 strains inhabit the human GI tract, based on estimates of 16S rRNA libraries from fecal samples . The application of second generation sequencing approaches, such as 454 pyrosequencing of 16S rRNA genes, has provided a greater depth of view of the composition of the gut microbiota (Andersson et al, 2008). One pyrosequencing study revealed as many as 3,300 unique OTUs in a single individual (Dethlefsen et al, 2008).…”
Section: Identification Of Microorganisms In the Gutmentioning
confidence: 99%
“…Consequently, more extensive studies on many different serpentine outcrops and on nonmetalliferous comparable soils (e.g. with low organic matter and high Mg/Ca ratio), analyzing high numbers of 16S rRNA libraries with next generation sequencing technologies (Andersson et al 2008;Droege and Hill 2008;Keijser et al 2008), should be performed to clarify if serpentine soils harbor significantly different taxonomic composition respective to non-metalliferous soils. Finally, given that a plant species has a completely different ecological and evolutionary connotation than a bacterial species, due to the high incidence of horizontal gene transfer (Gevers et al 2005;Konstantinidis et al 2006;Pace 2009;Staley 2006), these analyses may not necessarily show any taxonomic exclusiveness of serpentine soil: adaptation to serpentine in bacteria could be much more a matter of genes than of taxa.…”
Section: Bacterial Communities In Serpentine Soilmentioning
confidence: 99%
“…In addition to H. pylori, the stomach can also contain transient oral, esophageal or intestinal bacteria. To date, the few studies that have explored the microbiota of the human stomach using molecular methods (Bik et al, 2006;Andersson et al, 2008) have shown that the gastric community is highly dominated by Proteobacteria, Firmicutes, Actinobacteria and Bacteroidetes, with H. pylori being the single dominant bacteria in patients of positive H. pylori status. Bik et al (2006) sequenced 1833 bacterial clones from gastric biopsy samples from 23 US patients and found eight bacterial phyla (128 phylotypes) with no differences in richness by H. pylori status and with 7 of 11 patients of apparent negative H. pylori status having H. pylori clones.…”
Section: Introductionmentioning
confidence: 99%